2018
DOI: 10.1021/acs.jpcb.8b08223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origins of the Apparent Ideal CO2 Solubilities in Binary Ionic Liquid Mixtures

Abstract: Molecular dynamics (MD) simulations were conducted to investigate the variation of Henry’s constant of CO2 in two binary ionic liquid mixtures. One of the mixtures is formed by pairing the cation 1-n-butyl-3-methylimidazolium [C4mim]+ with chloride Cl– and methylsulfate [MeSO4]−, whereas the other binary ionic liquid mixture contains [C4mim]+ in combination with the anions Cl– and bis­(trifluoromethanesulfonyl)­imide [NTf2]−. In order to provide a microscopic understanding of the behavior of the Henry’s consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 52 publications
4
31
0
Order By: Relevance
“…For example, binary ionic liquid mixtures containing anions with a very substantial difference in β parameter have been reported to yield nonideal behavior in terms of excess molar volumes, viscosity, conductivity, and glass transition temperature experiments. ,, Our work and that of others have also shown that when binary ionic liquid mixtures with a common cation and two anions with a large difference in the hydrogen-bonding ability are formed, the molecular arrangement of anions around the cation in the mixture can markedly differ from those in the pure ionic liquids . We have also demonstrated that the presence of “non-native” arrangements of anions exert a profound influence on the physical dissolution mechanism of CO 2 at the molecular level …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…For example, binary ionic liquid mixtures containing anions with a very substantial difference in β parameter have been reported to yield nonideal behavior in terms of excess molar volumes, viscosity, conductivity, and glass transition temperature experiments. ,, Our work and that of others have also shown that when binary ionic liquid mixtures with a common cation and two anions with a large difference in the hydrogen-bonding ability are formed, the molecular arrangement of anions around the cation in the mixture can markedly differ from those in the pure ionic liquids . We have also demonstrated that the presence of “non-native” arrangements of anions exert a profound influence on the physical dissolution mechanism of CO 2 at the molecular level …”
Section: Introductionsupporting
confidence: 55%
“…11 We have also demonstrated that the presence of "non-native" arrangements of anions exert a profound influence on the physical dissolution mechanism of CO 2 at the molecular level. 12 Despite the significance of molar volumes and the hydrogenbonding ability of the anions in predicting the nonideal behavior in ionic liquid mixtures, it is surprising that a systematic investigation evaluating the influence of these markers has been absent in the literature. In the present work, we resort to molecular dynamics simulations to assess the ability of these two descriptors in providing clues to the nonideality in binary ionic liquid mixtures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This relation holds when the system is in the region x 2 or 1 -0. Since the above equation is valid when the binary system approaches x 1/2 -1, x 2/1 -0 for a species, so one will correct the calculated activity coefficient at infinite dilution (x 1/2 -0, x 2/1 -1) using the following relation ln g 1/2 (real) = ln g 1/2 (compute) = 1 + ln g 1/2 (model), (41) for which the minimum computed asymmetric interaction is less than 1 according to Appendix C.…”
Section: Appendix Bmentioning
confidence: 99%
“…4 Not surprisingly these ionic liquid mixtures have become very popular and are known to have a plethora of applications. [5][6][7][8][9][10][11][12][13][14] While the application of ionic liquid mixtures keeps growing, the fundamental knowledge of the interactions that occur in the system is only beginning to be acquired.…”
Section: Introductionmentioning
confidence: 99%